Optimal retirement asset decumulation strategies: The impact of housing wealth - Wei Sun; Robert K. Triest; Anthony Webb (Federal Reserve Bank of Boston, 2007)
We estimate the relationship between the returns on housing, stocks, and bonds, and simulate a variety of decumulation strategies incorporating reverse mortgages. We show that homeowner's reversionary interest, the amount that can be borrowed through a reverse mortgage, is a surprisingly risky asset. Under our baseline assumptions we find that the average household would be as much as 24 percent better off taking a reverse mortgage as a lifetime income relative to what appears to be the most common strategy: delaying tapping housing wealth until financial wealth is exhausted and then taking a line of credit. In addition, the results show that housing wealth displaces bonds in optimal portfolios, making the low rate of participation in the stock market even more of a puzzle.
Keywords: D14; D91; G11; J14; 330